Idiographic duo–trio tests using a constant-reference based on preference of each consumer: Sample presentation sequence in difference test can be customized for individual consumers to reduce error. (November 2016) - Kim, Min-A; Sim, Hye-Min; Lee, Hye-Seong
Abstract: As reformulations and processing changes are increasingly needed in the food industry to produce healthier, more sustainable, and cost effective products while maintaining superior quality, reliable measurements of consumers' sensory perception and discrimination are becoming more critical. Consumer discrimination methods using a preferred-reference duo–trio test design have been shown to be effective in improving the discrimination performance by customizing sample presentation sequences. However, this design can add complexity to the discrimination task for some consumers, resulting in more errors in sensory discrimination. The objective of the present study was to investigate the effects of different types of test instructions using the preference-reference duo–trio test design where a paired-preference test is followed by 6 repeated preferred-reference duo–trio tests, in comparison to the analytical method using the balanced-reference duo–trio. Analyses of d' estimates (product-related measure) and probabilistic sensory discriminators in momentary numbers of subjects showing statistical significance (subject-related measure) revealed that only preferred-reference duo–trio test using affective reference-framing, either by providing no information about the reference or information on a previously preferred sample, improved the sensory discrimination more than the analytical method. No decrease in discrimination performance was observed with any type of instruction, confirming that consumers could handle the test methods. These results suggest that when repeated tests are feasible, using the affective discrimination method would be operationally more efficient as well as ecologically more reliable for measuring consumers' sensory discrimination ability. Graphical abstract: Highlights: More efficient consumer discrimination method using repeated duo–trio was studied. Various method instructions of affective vs analytical reference schemes were tested. Affective methods using preferred-ref. idiographically optimized test sequences. Instruction informing previous preference facilitated affective use of constant-ref. More consumers could discriminate samples using such affective reference schemes.